Mathematical modeling of the forecast and standby heating modes - V. A. Tarasov; V. V. Tarasova; V. V. Afanasyev; V. G. Kovalev; V. N. Orlov (Известия высших учебных заведений: Проблемы энергетики)
The aim of the work is the development and study of methods for reducing the cost of heat energy for heating buildings and constructions by means of usage of automated control systems based on a programmable logic controller. Methods: In contrast to the known methods, the proposed mathematical model of non-stationary processes in heat-intensive enclosures makes it possible, according to the adaptive control algorithm, to perform forecast and standby heating taking into account the time dependence of the outdoor air temperature. Results: The algorithm ensures the equality of the heating system power and the heat losses power, allows one to maintain the desired indoor air temperature in the room when the outdoor air temperature changes. The heat loss compensation mode is achieved without using the temperature chart parameters of the network water and the parameters of proportional-integral-differential control laws that are necessary to set up at common automatic heating control systems. When calculating the forecast and standby heating modes, the mathematical model allows, at given initial and final temperatures of the internal air, determining the heating system power, which provide the desired temperature at the end of a specified period of time. The adaptive control algorithm allows setting the calculated outdoor temperature and the desired internal air temperature at any time. Under the forecast control, the mathematical model allows determining the system power at which the internal air temperature will remain almost constant when the outdoor air temperature changes. Conclusions: The developed algorithm of adaptive control allows one to create an energy-efficient heating system that provides the desired room temperature with minimum consumption of thermal energy taking into account all parameters affecting the heat loss power and the heating system power